THE COMPARISON OF LEARNING MODEL BETWEEN TWO STAY TWO STRAY AND GALLERY WALK CONCERNING ON STUDENTS’ CRITICAL THINKING ABILITY IN EXCRETION SYSTEM SUBJECT - Yeni Erikania; Arwin Achmad; Rini Rita T Marpaung (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2013)
The objective of this research was to find out the students’ critical thinking ability through TSTS and GW model in excretion system subject and students activity in teaching leaning process.The design of this research was pretest-posttest non equivalent. The research sample was students of XI IPA 1 as the first experimental class and XI IPA 2 as the second experimental class that was taken by cluster random sampling technique. The quantitative data was taken from pretest and posttest score and also N-gain that was analyzed by t-test on the level accurate of 95%. The qualitative data was the students’ critical thinking ability, data of students’ learning activities and questionnaire of students’ reaction on TSTS and GW model.The result of this research shown that TSTS model has been more increasing students’ critical thinking ability than GW model, it was shown by N-gain score on TSTS class (44,03) while in the GW class (32,30). The highest increasing indicator of students’ critical thinking ability was giving argument (32,74%), while the highest GW indicator was doing deduction (31,15%). The average of students’ activity in TSTS class was 84.44 while in GW class was 77,51. The highest activity in TSTS class and GW class occurred when changing information. Key words: Two Stay Two Stray, Gallery Walk, Critical thinking ability, Students’ activities, Excretion System